Assessing the Distributional Effects of the European Green Deal - Gustav Fredriksson; Georg Zachmann (CESifo Forum, 2021)
Achieving climate policy goals requires comprehensive measures to reduce greenhouse gas emissions, particularly in the energy and transport sectors. There are different ways to achieve the goals. Depending on which one policymakers choose, countries, industries or population groups will have to shoulder costs of the realignment. Who should bear more and who less of the burden? This edition of the CESifo Forum examines this critical and complex issue in the EU, the US, and in the low- and middle-income economies of the world. The authors also discuss ways how more socially-balanced and better politically-feasible energy and climate policies can be developed and implemented.
Keywords: 330